Impact of MM-Waves on the Different Cellular Levels of Wheat Seedlings - Nerkararyan, A. V.; L. A. Minasbekyan; M. R. Darbinyan
The phospholipids content of the nuclear envelope and the soluble nuclear fraction of the cells of wheat seedlings T. aestivum have been investigated. It is shown redistribution in the content of phospholipids in seedlings nuclear subfractions on the third day of germination after a single treatment of wheat seeds by extremely high frequency of electromagnetic irradiation (EHF EMI). It was revealed that under the influence of EHF EMI, total content of anionic phospholipids in the nuclear envelope is reduced, resulting in the changes of its permeability. In contrast to the nuclear envelope, in the matrix of the processing of mm-wave increases the total content of anionic phospholipids that can certainly cause a change in chromatin conformation. In our study have also shown that under the influence of mm-wave increased surface charge, which led to the changes in the electrokinetic potential (EKP) of cell nuclei in the electric-field gradient. Thus, as a result of mm-wave exposure, a potential difference between the outer and inner surfaces of the nuclei is formed due to the difference in content of anionic phospholipids between nuclear membrane and a matrix, which leads to the changes in membrane permeability.
Keywords: Physics; Cross-Disciplinary